Technical requirements for the application of economic intelligence and its impact On the dimensions of strategic success of banks: An applied research on a sample of Iraqi banks private (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This research sheds light on one of the important and vital topics for the banking sectors (technical requirements for the application of economic intelligence) namely by (Hardware, equipment, communication networks, software, databases). And the dimensions of the strategic success of the banks represented by(Customer satisfaction, customer trust, quality of service, growth) In the three Iraqi private banks, namely(Assyria International Investment, Mansour Investment, International Development Investment and Finance). Its implementation is an urgent necessity in order to improve the quality of its banking services to win the satisfaction of its customers and their confidence and then grow to achieve strategic success. This topic was selected for a number of justifications, the most important of which are the novelty of economic intelligence at the local level and the banking sector. In addition, to the lack of studies and research in it, so it was necessary to theoretical enrichment and applied analysis of this subject. The research problem was that the dynamics of the banking environment and the rapid changes and developments in ICTs, This has led to increased responsibilities on the banking sector towards communities it is impossible to survive and grow without relying on modern and sophisticated information systems. To reach its goals efficiently and effectively, this research was launched to solve the problem through the president's hypothesis, which stated that (There is a statistically significant correlation effect of the technical requirements for the application of economic intelligence in achieving strategic success). The historical descriptive, quantitative and statistical analytical approach and the questionnaire were used as a tool to collect data and information from the sample. (85) Who are in a position (Plenipotentiary Director, M. Plenipotentiary Director, Department Director, Department Director, M. Division Manager, Division Officer, Unit Officer). Use SPSS to calculate (Arithmetic mean, standard deviation, coefficient of variation, test F, determination coefficient R2, test X2, test t). The research reached the most important results is that the customer confidence dimension of the dimensions of strategic success has achieved the first place, and with a coefficient of difference amounted to(0.090) followed by growth after second place with a coefficient of difference of (0.105) After service quality, it was ranked third with a coefficient of difference of (0.112). It came after the customer satisfaction in the fourth and last rank with a difference factor of (0.180), the research also reached a number of conclusions, and most notably the technical requirements for the application of economic intelligence have an impact on the dimensions of strategic success.